Effects of Na2SeO3 and Na2SiO3 on Cd uptake and accumulation in two different rice (Oryza Sativa L.) cultivars at jointing stage - DAI Zou; YU Huaqing; GUO Changchun; MA Jun; LI Na; YANG Zhiyuan; XU Hui; SUN Yongjian (浙江大学学报. 农业与生命科学版)
Cadmium (Cd) is one of the most important inorganic pollutants in the soil of China and can be readily assimilated into plants and transported to human bodies through food chain. Rice is the staple food in China and also the major source of dietary Cd intake by people. Therefore, it’s important to decrease the uptake and accumulation of Cd in rice for human health. The capacity of iron plaque to sequester heavy metals is well known, besides its possible role as a buffer and reservoir in heavy metal uptake. It is well documented that exogenous Na2SeO3 or Na2SiO3 can depress the Cd absorption in rice by changing its content in the iron plaque, but the comparative study of exogenous Na2SeO3 or Na2SiO3 on Cd uptake in different rice cultivars is limited. The aim of this study is to explore the effects of Na2SeO3 and Na2SiO3 on depressing Cd assimilation in different rice cultivars.In this study, a pot experiment was conducted to explore the effects of Na2SeO3 or Na2SiO3 on Cd uptake in two rice cultivars with different grain Cd accumulation abilities. The seedlings were cultured in the soil with 5 mg/kg Cd (CdCl2· 2.5H2O) coupled with or without 1 mg/kg selenium (supplied as Na2SeO3) or 150 mg/kg silicon (supplied as Na2SiO3·9H2O), and were sampled at 42 days after transplanting and at mature stage, respectively. The biomass of roots and shoots, soil pH, Cd contents in the iron plaque, roots, shoots and grains at mature stage were measured.The results showed that exogenous Na2SiO3 significantly increased the pH of rhizosphere and depressed the root growth of the two rice cultivars. Exogenous Na2SeO3 improved the root biomass of Chuanguyou2348, but had no significant effect on the root biomass of Yixiangyou2115. The Cd content in the iron plaque of Chuanguyou2348 was significantly higher than that in Yixiangyou2115. The Cd content in the iron plaque was decreased by 8.5% and 14.1% in Yixiangyou2115, 12.9% and 39.4% in Chuanguyou2348 with the application of Na2SeO3 and Na2SiO3, respectively. Exogenous Na2SeO3 or Na2SiO3 also decreased the Cd content in the root and shoot of the two rice cultivars, and the Cd translocation coefficient from root to shoot decreased as well. Compared with the control, exogenous Na2SeO3 or Na2SiO3 also decreased the total Cd accumulation significantly, but their effects on the percentage distribution in different parts of rice were quite different. In Yixiangyou2115, Na2SeO3 and Na2SiO3 mainly increased the percentage of Cd in the iron plaque, but increased the Cd accumulation percentage in both the iron plaque and roots of Chuanguyou2348. Correlation analysis showed that Cd content in the iron plaque had positive correlation with Cd accumulation in rice roots and shoots, which indicated that iron plaque was a reservoir for Cd.It is concluded that exogenous Na2SeO3 or Na2SiO3 significantly affects the root growth of rice, decreases the Cd content and accumulation in rice root and shoot, then decreases the Cd content of the grain at mature stage in both the cultivars. Chuanguyou2348 has a larger decline than Yixiangyou2115 under the two treatments, and Na2SiO3 treatment shows better effect than Na2SeO3.